Low doses of steroid hormones and salmon gonadotropin induced oocyte maturation in catfish Heteropneustes fossilis - Nayak, P K; Mishra, J; Singh, B N; Ayyappan, S (Indian Journal of Fisheries, 2011)
The effects of low doses of salmon gonadotropin (SG-GIOO) and three steroids, 17a-20|3-dihydroxy progesterone (17a-20pP), deoxycorticosterone (DOC) and progesteroneindividually or in combinations of steroid with SG-GlOO, on ovulation andhatching in Heteropneustes fossilis (Bloch) were investigated. Steroids at any ofthe three different dose levels (1, 1.5 and 2)ig/g b.w.) could not induce ovulationwhen injected alone. 8(3—GlOO at a dose level of 10 pg/g b.w. was not effective,whereas at the dose level of 15 pg/g b.w. could induce ovulation. All the threesteroids at their lowest doses (Ipg/g b.w.) when injected in combination withSG-GIOO (lOpg/g b.w.) were significantly effective in inducing ovulation. The17a-20pP in combination with SG-GIOO showed most effective combination ascompared to the other treatments when hatching percentage was taken intoaccount.